Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/admi.202100718
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Engineered n‐Doping of WSe2 via Argon Plasma Treatment and Its Application in Field‐Effect Transistors

Abstract: limits the further downscaling of Si-based electronic devices. 2D layered materials have attracted significant attention as post-Si nanoelectronic materials owing to their intriguing properties such as atomic thickness, having no dangling bond in a surface, high surface-to-volume ratio, and immunity to the short-channel effect. [1] Among the various 2D materials, 2H transition metal dichalcogenides (TMDCs), represented by MoS 2 and WSe 2 , are promising candidates for next-generation semiconductor materials in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…Defects, such as Se vacancies, can induce n‐type doping. [ 33 , 34 ] However, the formation of Se vacancies requires a high‐energy process, for example, Ar + plasma treatment or strong e‐beam irradiation with an ultrahigh dose (>4000 µC cm –2 ) typically used in transmission electron microscopy (TEM). Our e‐beam irradiation used the standard EBL process with a low area dose (≈600 µC cm –2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defects, such as Se vacancies, can induce n‐type doping. [ 33 , 34 ] However, the formation of Se vacancies requires a high‐energy process, for example, Ar + plasma treatment or strong e‐beam irradiation with an ultrahigh dose (>4000 µC cm –2 ) typically used in transmission electron microscopy (TEM). Our e‐beam irradiation used the standard EBL process with a low area dose (≈600 µC cm –2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our e‐beam irradiation used the standard EBL process with a low area dose (≈600 µC cm –2 ). [ 33 , 34 , 35 ] Matsunaga et al. found that a low‐energy e‐beam created an S vacancy‐induced strain in the MoS 2 crystal, which modified the bandgap of MoS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The n-doping of intrinsically ambipolar multilayer-WSe 2 in the contact region was achieved by intentionally creating Se vacancies that can act as a donor site near the edge of the conduction band (shallow defect bands) by using a mild Ar-ion bombardment. , Tosun et al reported that the Fermi level of n-doped WSe 2 by the mild H 2 plasma treatment was estimated to be 10 meV below the conduction band edge . Kim et al reported that 0.33 and 0.46 eV defect levels of Se vacancy were generated below the conduction band under the mild Ar-ion plasma treatment. The defect engineering is advantageous for doping atomically thin 2D materials, in which case, the conventional ion implantation method is inappropriate.…”
Section: Resultsmentioning
confidence: 99%
“…32,34 Tosun et al reported that the Fermi level of n-doped WSe 2 by the mild H 2 plasma treatment was estimated to be 10 meV below the conduction band edge. 34 Kim et al 35 reported that 0.33 and 0.46 eV defect levels of Se vacancy were generated below the conduction band under the mild Ar-ion plasma treatment. The defect engineering is advantageous for doping atomically thin 2D materials, in which case, the conventional ion implantation method is inappropriate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[8] quite prominent, indicating its possible application in nonlinear and nonreciprocal optical devices. [17] Point defects have significant influence on physical and chemical properties of 2D materials [18][19][20][21][22][23][24] and are important with respect to the performance of devices. Various types of point defects in CrI 3 monolayer, including Cr vacancy and I vacancy, have been investigated theoretically.…”
Section: Introductionmentioning
confidence: 99%